Answer:
![x=2.4](https://tex.z-dn.net/?f=x%3D2.4)
Step-by-step explanation:
<u>Solving Equations Using Successive Approximations</u>
We need to find the solution to the equation
![f(x)=g(x)](https://tex.z-dn.net/?f=f%28x%29%3Dg%28x%29)
where
![f(x)=2x-5](https://tex.z-dn.net/?f=f%28x%29%3D2x-5)
![g(x)=x^2-6](https://tex.z-dn.net/?f=g%28x%29%3Dx%5E2-6)
The approximation has been already started and reached a state for x=2.5 where
![f(2.5)=0](https://tex.z-dn.net/?f=f%282.5%29%3D0)
![g(2.5)=2.5^2-6=0.25](https://tex.z-dn.net/?f=g%282.5%29%3D2.5%5E2-6%3D0.25)
The difference between the results is 0.25, we need further steps to reach a good solution (to the nearest tenth)
Let's test for x=2.4
![f(2.4)=-0.2](https://tex.z-dn.net/?f=f%282.4%29%3D-0.2)
![g(2.4)=2.4^2-6=-0.24](https://tex.z-dn.net/?f=g%282.4%29%3D2.4%5E2-6%3D-0.24)
The new difference is -0.2+0.24=0.04
It's accurate enough, thus the solution is
![\boxed{x=2.4}](https://tex.z-dn.net/?f=%5Cboxed%7Bx%3D2.4%7D)
Good question , don’t really know but use photo math or there’s an link for you
Answer:
3 square root 2.
Step-by-step explanation:
I think the answer is b (3 square root 2). the Pythagorean therom states that B^2+ B^2= C^2. we know that c squared is 36. 3 square root 2 is approximately 4.24. ( this squared is 17.98). 17.98 + 17.98 = 35.96. If i round this up, it is 36.
The simplified form for (3x² + 2y² - 5x + y) + (2x² - 2xy - 2y² -5x + 3y) is (5x² + 0y² - 10x + 4y - 2xy).
<h3>A quadratic equation is what?</h3>
At least one squared term must be present because a quadratic is a second-degree polynomial equation. It is also known as quadratic equations. The answers to the issue are the values of the x that satisfy the quadratic equation. These solutions are called the roots or zeros of the quadratic equations. The solutions to the given equation are any polynomial's roots. A polynomial equation with a maximum degree of two is known as a quadratic equation, or simply quadratics.
<h3>How is an equation made simpler?</h3>
The equation can be made simpler by adding up all of the coefficients for the specified correspondent term through constructive addition or subtraction of terms, as suggested in the question.
Given, the equation is (3x² + 2y² - 5x + y) + (2x² - 2xy - 2y² -5x + 3y)
Removing brackets and the adding we get,
3x² + 2x² + 2y² - 2y² + (- 5x) + (- 5x) + y + 3y + (- 2xy) = (5x² + 0y² - 10x + 4y - 2xy)
To learn more about quadratic equations, tap on the link below:
brainly.com/question/1214333
#SPJ10